Optimization of carbon ion and proton treatment plans using the raster-scanning technique for patients with unresectable pancreatic cancer - Dreher, Constantin (Radiat Oncol, 2015)
BACKGROUND: The aim of the thesis is to improve radiation plans of patients with locally advanced, unresectable pancreatic cancer by using carbon ion and proton beams. PATIENTS AND METHODS: Using the treatment planning system Syngo RT Planning (Siemens, Erlangen, Germany) a total of 50 treatment plans have been created for five patients with the dose schedule 15 × 3 Gy(RBE). With reference to the anatomy, five field configurations were considered to be relevant. The plans were analyzed with respect to dose distribution and individual anatomy, and compared using a customized index. RESULTS: Within the index the three-field configurations yielded the best results, though with a high variety of score points (field setup 5, carbon ion: median 74 (range 48–101)). The maximum dose in the myelon is low (e.g. case 3, carbon ion: 21.5 Gy(RBE)). A single posterior field generally spares the organs at risk, but the maximum dose in the myelon is high (e.g. case 3, carbon ion: 32.9 Gy(RBE)). Two oblique posterior fields resulted in acceptable maximum doses in the myelon (e.g. case 3, carbon ion: 26.9 Gy(RBE)). The single-field configuration and the two oblique posterior fields had a small score dispersion (carbon ion: median 66 and 58 (range 62–72 and 40–69)). In cases with topographic proximity of the organs at risk to the target volume, the single-field configuration scored as well as the three-field configurations. CONCLUSION: In summary, the three-field configurations showed the best dose distributions. A single posterior field seems to be robust and beneficial in case of difficult topographical conditions and topographical proximity of organs at risk to the target volume. A setup with two oblique posterior fields is a reasonable compromise between three-field and single-field configurations.